Web Based Cloud Hosting Service Using Xcode Hoster - Fitriani, Wirda; Lubis, Syahrian; Lubis, Akhyar (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Demand for efficient, reliable, and easily accessible cloud hosting services continues to increase. Xcodehoster is a web-based cloud hosting platform designed to meet these needs. This research aims to evaluate the adoption process of Xcodehoster as a cloud hostingservices at an organizational scale. This was done by identifying key user needs, analyzing Xcodehoster’s features and advantages, and comparing it with other cloud hosting platforms. The methods used in this research include a literature review and direct testing of Xcodeshoster. The result of this research indicate that Xcodehoster has significant potential in improving operational efficiency and reducing IT infrastructer costs. Furthermore, its ease of use and reliable technical support make Xcodehoster an attractive option for organizations.